Interest to learn music among non-music students in secondary school / Ramio Pangkat - Pangkat, Ramio (Faculty of Music, 2009)
Interest to learn music in school, especially at the secondary level poses many issues in Malaysia. The fact that not many secondary schools offer the subject offers less opportunity for secondary students to choose to learn music. However, for the schools which offer music, one may assume that students would take the opportunity to select to take music. The purpose of this study is to determine the perception of secondary students towards music learning and factors that influence non-music students' interest to leam music in secondary school. A total of 175 participants participated, consisting of 106 female students and 69 are male students. A questionnaire was used to gather data from the subjects. With the adaptation of the expectancy-value model of motivational theory by Eccles & Wigfield (1988), seven-point Likert scale with different motivational construct of the expectancy value theory such as importance, usefulness, enjoyment and difficulty in implementing the interest to leam music subjects in school, could be measured. Findings show that there are various factors that influence non-music students' interest to leam music. These factors are themselves, music activities, teacher, parent, and peers. It is found that most non-music students would be interested to leam music at school if they were given the chance to study it. Most of non-music students perceive that music learning in school is very enjoyable and very important to them especially in playing a music instrument. Overall, it shows that most non-music students in school show high interest towards studying and playing a music instru